1991
DOI: 10.1128/mcb.11.6.3307
|View full text |Cite
|
Sign up to set email alerts
|

The CYC8 and TUP1 proteins involved in glucose repression in Saccharomyces cerevisiae are associated in a protein complex.

Abstract: Mutations of the yeast CYC8 or TUPI genes greatly reduce the degree of glucose repression of many genes and affect other regulatory pathways, including mating type. The predicted CYC8 protein contains 10 copies of the 34-amino-acid tetratricopeptide repeat unit, and the predicted TUP1 protein has six repeated regions found in the I8 subunit of heterotrineric G proteins. The absence of DNA-binding motifs and the presence of these repeated domains suggest that the CYC8 and TUP1 proteins function via protein-prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
140
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(143 citation statements)
references
References 44 publications
3
140
0
Order By: Relevance
“…The peak fractions were pooled and further fractionated by gel filtration. As determined by Western immunoblotting, Ssn6HIS and Tup1 were among the first proteins to flow through the filtration column, consistent with the results of Williams et al (18) that these proteins are present together in a large complex (Fig. 1A, fraction 9 and 10).…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…The peak fractions were pooled and further fractionated by gel filtration. As determined by Western immunoblotting, Ssn6HIS and Tup1 were among the first proteins to flow through the filtration column, consistent with the results of Williams et al (18) that these proteins are present together in a large complex (Fig. 1A, fraction 9 and 10).…”
Section: Resultssupporting
confidence: 76%
“…Fig. 1C shows the purified proteins on a silver- Determination of the Size of the Ssn6-Tup1 Complex-It has been suggested that the previous estimate of the molecular mass of the Ssn6-Tup1 complex of 1.2 MDa may be an overestimate if the complex is elongated or extended (18). Glycerol gradient sedimentation in conjunction with gel filtration can be used to estimate the molecular mass of a molecule with greater accuracy than can either method alone (32).…”
Section: Ssn6-tup1 Repression Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…In the presence of glucose, the GAL cluster is repressed via association of glucose-dependent transcription factors, Mig1 and Nrg1, and the associated Tup1/Cyc8 (Tup1/Ssn6) co-repressor complex. 42,43 In the presence of galactose, the Gal4 transcriptional activator associates with GAL genes and facilitates transcriptional activation by promoting recruitment of co-activators and RNA polymerase II (RNA P II). 44 The third transcriptional state, called the "derepressed" or "non-induced" state, occurs when yeast are grown in the presence of raffinose.…”
mentioning
confidence: 99%
“…WD repeats typically contain a GH dipeptide 11-24 residues from the N-terminus, and the WD dipeptide at the C-terminus. Proteins with WD repeats have diverse functions, such as signal transduction, RNA processing, transcription, cytoskeleton assembly and mitotic-spindle formation, regulation of vesicle formation and vesicular trafficking, control of various aspects of cell division, and the regulation of sulfur metabolism in fungi [9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%